2012
DOI: 10.1038/pj.2012.18
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced mendable network polymer from poly(butylene adipate) end-functionalized with cinnamoyl groups

Abstract: A network polymer with photoinduced mending abilities was prepared from cinnamoyl-telechelic prepolymer of poly(butylene adipate), PBAC 2 , and a tetra-cinnamoyl linker, C 4 , by photodimerization. The photodimerization reaction of the cinnamoyl groups was analyzed using both ultraviolet (UV)/visible (vis) and infrared (IR) spectroscopy. In the reaction, the isomerization of the cinnamate group from the trans to the cis conformation competes with the dimerization reaction of cinnamates. The fractions of dimer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 24 publications
(20 reference statements)
0
32
0
Order By: Relevance
“…Ling et al demonstrated a self‐healing polyurethane network with coumarin sidechains, which can be cleaved upon irradiation with UV light at 254 nm and reform the crosslinks at 350 nm . The characteristic of cinnamate groups, as described by Yoshie and co‐workers is the mechanism of photoisomerization, which occurs alongside the dimerization . In order to overcome the isomerization, since this can be problematic for some polymers if only one of the isomers is reactive toward addition, examples of [4 + 4] cycloaddition in reversible covalent polymer networks have been described.…”
Section: Design Principles Of Intrinsic Healable Polymer Systemsmentioning
confidence: 99%
“…Ling et al demonstrated a self‐healing polyurethane network with coumarin sidechains, which can be cleaved upon irradiation with UV light at 254 nm and reform the crosslinks at 350 nm . The characteristic of cinnamate groups, as described by Yoshie and co‐workers is the mechanism of photoisomerization, which occurs alongside the dimerization . In order to overcome the isomerization, since this can be problematic for some polymers if only one of the isomers is reactive toward addition, examples of [4 + 4] cycloaddition in reversible covalent polymer networks have been described.…”
Section: Design Principles Of Intrinsic Healable Polymer Systemsmentioning
confidence: 99%
“…In their study, healing was conducted by photoirradiation (λ > 280 nm) for 10 minutes. More recently, Ling et al and Oya et al continued this line of research by synthesizing novel self-healing polymers based on [2+2] photocycloaddition [49,50].…”
Section: Photochemical Triggered Self-healingmentioning
confidence: 99%
“…Figure 1(a) displays the UV absorbance variation of TCE dilute solution as a function of UV exposure time. It had strong UV absorbance between 250 and 350 nm with a peak centered at approximately 280 nm; this likely corresponds to the abundance of π-π* transitions of the C=C double bond from cinnamoyl groups before photoirradiation, as reported elsewhere 26,[32][33] . The change in the absorbance value was monitored for continual irradiation, and it is obvious to notice that the absorbance band decreases rapidly with exposure time and disappears almost completely within 30 minutes of photoirradiation.…”
Section: Photoreaction Of Tce and Pvcimentioning
confidence: 99%